Impacts of the Covid-19 Pandemic in inner areas: Remote work and near-home tourism through mobile phone data in Piacenza Apennine - Lanza, Giovanni; Pucci, Paola; Carboni, Luigi; Vendemmia, Bruna (TeMA - Journal of Land Use, Mobility and Environment, 2022)
<span class="NormalTextRun SCXW13509994 BCX0" data-ccp-parastyle="PARAGRAPH" data-ccp-parastyle-defn=""ObjectId":"00000000-0000-0000-0000-000000000000|0","ClassId":1073872969,"Properties":[469775450,"PARAGRAPH",201340122,"2",134234082,"true",134233614,"true",469778129,"PARAGRAPH",335572020,"1",469777841,"Tahoma",469777842,"Tahoma",469777843,"SimSun",469777844,"Tahoma",469769226,"Tahoma,SimSun",335557856,"16777215",268442635,"18",335559705,"1033",335551547,"1033",335559740,"336",201341983,"0",335551550,"6",335551620,"6",469777929,"PARAGRAPH Carattere",469778324,"Normal",469778325,"["PARAGRAPH INDENT"]"]" data-ccp-parastyle-linked-defn=""ObjectId":"00000000-0000-0000-0000-000000000000|0","ClassId":1073872969,"Properties":[469775450,"PARAGRAPH Carattere",201340122,"1",134233614,"true",469778129,"PARAGRAPHCarattere",335572020,"1",134231262,"true",469777841,"Tahoma",469777842,"Tahoma",469777843,"SimSun",469777844,"Tahoma",469769226,"Tahoma,SimSun",268442635,"18",335551547,"1033",469777929,"PARAGRAPH"]">While the impacts of the Covid-19 outbreak on urban areas have been deeply investigated, the effects of the virus on sparsely populated and marginal areas are still poorly explored. In Italy, those “inner” areas are often characterized by processes of marginalization due to aging and loss of population, low occupational rate and income, a progressive deprivation of local know-how, and the shrinking of essential services. Yet, a reverse migration from urban centers to rural and peripheral areas has been reported worldwide among the main effects of the Covid-19 pandmic, being in some cases an opportunity to slow down and even reverse the process of marginalization. By combining mobile phone and socio-spatial data, this paper aims to analyze the space-time variability of human presence before and during the Covid-19 lockdown in the Apennine area of the e province of Piacenza, a representative case of Italy’s inner areas, to read if and how the pandemic has contributed to modify the rhythms and trends of those territories. Two dynamics have been investigated: remote and near-home tourism. In addition to provide a picture of the changes that occurred in these marginal contexts, the outcomes have shown the great potentiality of mobile phone data, along with some limits that may prejudice their usability, particularly for territorial research in low-density areas.